"Science and proven experience": How should the epistemology of medicine inform the regulation of healthcare?. Issue 8 (August 2020) - Wallin, Annika; Wahlberg, Lena; Persson, Johannes; Dewitt, Barry
Highlights: Swedish medico-legal conception "proven experience" is operative in medical malpractice and compensation cases. Survey on random sample of Swedish health care professionals reveals a medico-legal conflict. "Proven experience" is regarded as definitionally unclear, but definitional power is withheld from legal professionals. Normative-descriptive-prescriptive framework suggested to resolve conflict between actual and perceived definitional power. Abstract: The Swedish medico-legal concept of "science and proven experience" is both legally important and ambiguous. The conceptual uncertainty associated with it can hamper effective assessment of medical evidence in legal proceedings and encourage medical professionals to distrust legal regulation. We examine normative criteria a functioning medico-legal notion should presumably meet, e.g. clarity, acceptability and consistency with existing laws. We also survey healthcare professionals to see how they understand science and proven experience and thus determine the extent to which their understanding meets the normative criteria. The survey suggests that medical professionals feel more certain about "science and proven experience" in the medical context than they do in a legal context. They still have substantial trust in the legal use of the notion, but they do not believe that legal professionals should be allowed to determine the meaning of "science and proven experience" in the legal context. With these results in mind, we argue that the best way to meet the normative criteria and resolve conceptual uncertainty is to specify sub-questions that clarify the notion. We recommend an analytical-deliberative approach that will close the gap between the medical and legal professions' perceptions of how law and medicine relate.